Government and Civil Society Partnership in Waste Bank Program in Kediri, Indonesia - Wijaya, Andy Fefta; Mindarti, Lely Indah; Permana, I Made Dwi (Journal of Public Administration Studies, 2016)
This research is aimed to address how the patterns of partnership between government and civil society in waste bank program in Perumahan Wilis Indah II Kota Kediri, how its role, the process of what has been conducted in achieving the success of the partnership, and the benefits of each actor and the target group that existence in the partnership. This study used qualitative approach, particularly descriptive analysis. Primary data was collected from interviews, and field observations. Secondary data was collected from documents to complement primary data related to the focus of research such as Act No. 18 Year 2008, Mayor Regulations, Mayor Decisions, Head of SKPD Decisions, RPJMD Kota Kediri, Kediri Waste Characteristic Studies, and Kediri in Figures. This study revealed the partnership amongst government, private, and society use principle of mutual benefit partnership with synergistic partnership. The roles of government, civil society, and NGOs in general they are together make planning and execute the project. In particular, the government has roles as a motivator, endorsement of commitment, setting the rule and law, and also accompany to both physical and non-physical action. For the NGO role is providing assistance in physical and non-physical action and society as waste bank operator. Based on the process condition theory of which is states that to ensure the success of the partnership there are 12 conditions that should be fulfill, in fact the partnership in waste bank of Sri Wilis Kediri is not all the same as in theory.